2004
DOI: 10.1002/app.20024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of organic–inorganic hybrids based on epoxy resin and 3‐glycidyloxypropyltrimethoxysilane

Abstract: Organic-inorganic hybrid materials based on diglycidyl ether of bisphenol A (DGEBA) and 3-glycidyloxypropyltrimethoxysilane (GLYMO) were prepared, using a poly(oxypropylene) diamine Jeffamine D230 as a curing agent. Materials were studied by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), infrared spectroscopy, swelling in tetrahydrofurane (THF), and Soxhlet extraction in THF. A dependence of the final conversion of epoxy groups and the final degree of organic phase crosslinking on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 25 publications
0
24
1
3
Order By: Relevance
“…On the other hand, the CNT presence in the epoxy/silsesquioxane matrixes did not favored the degradation of theses matrices, confirming the higher thermal stability provided by silsesquioxanes 5,9 .…”
Section: Samplesmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, the CNT presence in the epoxy/silsesquioxane matrixes did not favored the degradation of theses matrices, confirming the higher thermal stability provided by silsesquioxanes 5,9 .…”
Section: Samplesmentioning
confidence: 87%
“…Furthermore, a decrease in the T g value with the incorporation of a random 5,7,8,29 or organized polysilsesquioxane structures 2,30,31 in epoxy matrix have been reported in literature. On the other hand, in our previous work 13 , the incorporation of the APTES/PTES copolysilsesquioxane provided improvement on T g up to 13 °C in relation to neat LY matrix.…”
Section: Thermal Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Macan et al [20,21] have studied the influence of silica network produced from the sol-gel process on the cure kinetics of epoxies in THF using the different techniques. They observed that inorganic phase influence the cure kinetics thus hindering the cross-linking of organic phase.…”
Section: Introductionmentioning
confidence: 99%
“…The filler-matrix interface also plays an important role; if the T g of the interface is less than that of the matrix, the T g of the resulting composite may decrease, but if the T g of the interface is higher than that of the matrix, the T g of composite will increase by increasing filler content [29]. The silanes used previously [6,[19][20][21][22][23]27] to compatiblize the organic inorganic phases (e.g., 3-aminopropyl-triethoxysilane, N-(2-aminoethyl)-3-aminopropyl-trimethoxysilane, 3-glycidoxy propyl-trimethoxysilane) had the propyl chain as interface which is considered to be very flexible. We in the present paper have used instead aminophenyl-trimethoxysilane (APTMOS) where the phenyl group acting as inter-phase is more rigid than the propyl chain used previously.…”
Section: Introductionmentioning
confidence: 99%